SC-FDMA for mobile communications - Abd el-Samie, Fathi E.; Al-Kamali, Faisal S.; Al-nahari, Azzam Y.; Dessouky, Moawad I. (Taylor & Francis, 2014)
This book examines Single-Carrier Frequency Division Multiple Access (SC-FDMA). Exploring the emerging trend of cooperative communication and how it can improve the physical layer security, it considers the design of distributed coding schemes and protocols for wireless relay networks where users cooperate to send their data to the destination. It proposes a cooperative diversity protocol implementing space-time coding for an arbitrary number of relay nodes with Amplify-and-Forward (AF) protocol. It considers the design of a distributed Space-Frequency Code (SFC) for multipath fading relay channels that can exploit both cooperative and multipath diversities. It also investigates the design of cooperative diversity schemes for the SC-FDMA system in the uplink direction